Incidence, predictors and clinical impact of permanent pacemaker insertion in women following transcatheter aortic valve implantation: Insights from a prospective multinational registry. Issue 6 (12th June 2021) - Nicolas, Johny; Guedeney, Paul; Claessen, Bimmer E.; Mehilli, Julinda; Petronio, Anna Sonia; Sartori, Samantha; Lefèvre, Thierry; Presbitero, Patrizia; Capranzano, Piera; Iadanza, Alessandro; Cao, Davide; Chiarito, Mauro; et al.
Abstract: Objectives: To describe the incidence, predictors, and clinical impact of permanent pacemaker insertion (PPI) following transcatheter aortic valve replacement (TAVR) in women. Background: Data on pacemaker insertion complicating TAVR in women are scarce. Methods: The Women's International Transcatheter Aortic Valve implantation (WIN‐TAVI) is a prospective registry evaluating the safety and efficacy of TAVR in women. We included patients without preprocedural pacemakers and divided them into two groups: (1) PPI and (2) no‐PPI. We identified PPI predictors using logistic regression and studied its clinical impact on the Valve Academic Research Consortium (VARC)‐2 efficacy and safety endpoints. Results: Out of 1019 patients, 922 were included in the analysis. Post‐TAVR PPI occurred in 132 (14.3%) patients. Clinical and procedural characteristics were similar in both groups. Pre‐existing right bundle branch block (RBBB) was associated with a high risk of post‐TAVR PPI (OR 3.62, 95% CI 1.85–7.06, p < 0.001), while implantation of balloon‐expandable prosthesis was associated with a lower risk (OR 0.47, 95% CI 0.30–0.74, p < 0.001). Post‐TAVR PPI prolonged in‐hospital stay by a median of 2 days (11 [9–16] days in PPI vs. 9 [7–14] days in no‐PPI, p = 0.005), yet risks of VARC‐2 efficacy and safety endpoints at 1 year were similar in both groups (adj HR 0.95, 95% CI 0.60–1.52, p = 0.84 and adj HR 1.22, 95% CI 0.83–1.79, p = 0.31, respectively). Conclusion: Pacemaker implantation following TAVR is frequent among women and is associated with pre‐existing RBBB and valve type. PPI prolongs hospital stay, albeit without any significant impact on 1‐year outcomes.